Development of on-line rotational speed monitor system of TBM disc cutter. (August 2016) - Lan, Hao; Xia, Yimin; Zhu, Zongming; Ji, Zhiyong; Mao, Jinsong
Abstract: Disc cutter is the main rock breaking tool of TBM. It is angled worn frequently because of locked-rotor; as a result, monitoring relevant operating parameters of TBM disc cutter has become an urgent technical problem. This paper studies nondestructive and non-contact online detection disc cutter rotational speed method of based on eddy current sensor: applies eddy current sensor to detecting six 2 mm-high metal bumps setting on the disc cutter, so as to detect the rotational speed of disc cutter. K60 MCU is applied as the main control core. The experimental results show that the on-line rotational speed monitor system of disc cutter features high anti-jamming ability and is reliable.